Glial Derived Neurotrophic Factor and Schizophrenia Spectrum Disorders: A Scoping Review - Ricci, Valerio; De Berardis, Domenico; Martinotti, Giovanni; Maina, Giuseppe (Current Neuropharmacology, 2025)
BackgroundPsychotic disorders, characterized by altered brain function, significantly impair reality perception. The neurodevelopmental hypothesis suggests these disorders originate from early brain development disruptions. Glial-derived neurotrophic factor (GDNF) is crucial for neuronal survival and differentiation, especially in dopaminergic neurons, and shows promise in neurodegenerative and neuropsychiatric conditions.ObjectivesThis scoping review aims to examine the role of GDNF in schizophrenia spectrum disorders and substance-induced psychoses, integrating knowledge on the neurobiological mechanisms and therapeutic potential of GDNF.MethodsA comprehensive literature search was conducted using PubMed and Scopus databases from January 2001 onwards. Data extraction focused on GDNF levels, cognitive function, antipsychotic treatment effects, and genetic studies.ResultsThe review included 25 studies (18 human, 7 animal). While some studies demonstrated inconsistent results regarding GDNF serum levels in schizophrenic patients, the majority reported correlations between GDNF levels and cognitive functions. Animal studies underscored GDNF's role in stress response, drug-induced neurotoxicity, and dopamine signaling abnormalities. Genetic studies revealed potential associations between GDNF gene polymorphisms and schizophrenia susceptibility, though findings were mixed.DiscussionGDNF plays a significant role in cognitive functions and neuroprotection in schizophrenia. The variability in study results underscores the complexity of GDNF's involvement. The therapeutic potential of GDNF in psychotic disorders remains unclear, necessitating further research to clarify its efficacy and safety.ConclusionThis review emphasizes the importance of integrated biomarker strategies, gene therapy approaches, and precision medicine in advancing the understanding and treatment of psychotic disorders.
Keywords: neurotrophic factors